Domestic Violence and COVID-19 in Austria: increased vulnerability and risk for children and young people - Potkanski-Palka, Monika (SIAK-Journal, 2021)
Domestic violence includes all forms of physical, sexual, psychological or economic violence and affects people of all genders and ages. It usually takes place within the family and the household. Domestic violence during pandemics such as the current COVID-19 pandemic is associated with economic stress, disaster-related instability, increased exposure to exploitative relationships, and reduced options for support (Usher et al. 2020, 549). Social isolation and reduction of social contacts in order to reduce the spread of COVID-19 aggravate the living conditions of vulnerable groups such as (young) children and teenagers. Despite a statement by Karl Nehammer (ÖVP) the Federal Minister of the Interior and Susanne Raab (ÖVP), at the time Federal Minister for Women and Integration claiming that the number of cases of domestic violence has not increased in Austria during the COVID-19 pandemic, the following study, as well as other similar international studies, paints an entirely different picture. The ten teachers interviewed for this study all share the belief that the lockdowns have led to an increase in violence in certain families, in particular families with a low socio-economic status and in which violence was already prevalent before the pandemic started.